Storytelling Variations and Student Writing Ability in Madrasah Ibtidaiyah - Fuad, A. Jauhar (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
This paper is to find out learning that uses fairy tale methods and increase students' literacy skills in rewriting the contents of fairy tales. Researchers use classroom action research. Data collection techniques with observation and writing ability tests, with skinative and quantitative analysis techniques. Research findings: there is an increase in the ability to rewrite fairy tales read from cycle I to cycle II. There are variations in storytelling techniques by utilizing various learning media in the form of images, audio visuals and the surrounding environment.